Pengaruh Kecemasan Matematika (Mathematics Anxiety) terhadap Hasil Belajar Matematika Siswa SD - Mukhlisa, Nurul; Zainal, Zaid; Paulina, Lusmarpi (SOCIETIES: Journal of Social Sciences and Humanities, 2024)
Abstract. This research is ex post facto quantitative research with a correlational type, which aims to determine the effect of mathematics anxiety on mathematics learning achievement for elementary school students in Mattirowalie Village, Wajo Regency. The population in this research were all high-grade elementary school students in Mattirowalie Village, Wajo Regency, totaling 151 people. In comparison, the sample in this research was 110 people with the use of proportional random sampling. The data analysis technique used is simple linear regression analysis. Based on the results of inferential analysis, a significance value is 0.002 <0.05, then H0 is rejected, which means that there is an influence of mathematics anxiety on student mathematics learning achievement for elementary school students in Mattirowalie Village, Wajo Regency. The regression equation Y = 90.641 – 0.243 X, meaning that the average score of the student's mathematics learning achievement has changed by 0.243 for each unit of change that occurs in math anxiety. Keywords: Mathematics anxiety, learning achievements, mathematics.